A judicial review of the inactivity of public administration in the Slovak Republic - Horvat, Matej (The Opole Studies in Administration and Law, 2019)
The article focuses on inactivity of the public administration in the Slovak Republic. It analyses this malfunction of the public administration from the point of view of the legal theory, international legal regulation as well as national legal regulation. The emphasis is on the national legal regulation that should provide effective legal remedies on how to eliminate inactivity of the public administration – namely the Constitution of the Slovak Republic, the Act on Administrative Proceeding and the Act on Administrative Justice Procedure. The article analyses the new legal regulation on a judicial review of inactivity stipulated in the Act on Administrative Justice Procedure and compares it with the previous legal regulation. The aim is to conclude which legal regulation is more effective and describe why it is so.